Elevated Glucose Challenge Test in a Nondiabetic Index Pregnancy and Gestational Diabetes in a Subsequent Pregnancy - de Los Reyes, Samantha; Dude, Annie; Adams, Marci; Plunkett, Beth; Hirsch, Emmet (American Journal of Perinatology, 2021)
Objective The aim of this study was to evaluate whether a 1-hour glucose challenge test (GCT) ≥140 mg/dL in a nondiabetic index pregnancy is associated with the development of gestational diabetes mellitus (GDM) in a subsequent pregnancy.Study Design We performed a retrospective cohort study from a single institution from June 2009 to December 2018. Women with a nondiabetic index singleton gestation who underwent a 1-hour GCT at 24 to 28 weeks and had a successive singleton delivery were included. GDM was defined by a 1-hour GCT of ≥ 200 mg/dL, ≥2 of 4 elevated values on a 3-hour GCT, or a diagnosis of GDM defined by International Classification of Disease codes in the electronic medical record. Univariable analyses were performed to evaluate the associations between an elevated 1-hour GCT result in the index pregnancy, maternal characteristics, and the development of GDM in the subsequent pregnancy. Variables found to be significant (p < 0.05) were included in multivariable analysis.Results A total of 2,423 women were included. Of these, 340 (14.0%) had an elevated 1-hour GCT in the index pregnancy. Women with an elevated 1-hour GCT in the index pregnancy compared with those without were significantly more likely to be older, married, privately insured, of Hispanic ethnicity or Asian race, chronically hypertensive, have a higher body mass index (BMI), have a shorter inter-pregnancy interval, and to develop GDM in the subsequent pregnancy (14.4 vs. 3.3%, p < 0.001). In multivariable analysis, an elevated 1-hour GCT (adjusted odds ratio [aOR]: 4.54, 95% confidence interval [CI]: 3.02–6.81), first-trimester BMI ≥30 kg/m2 in the index pregnancy (aOR: 3.10, 95% CI: 2.03–4.71), Asian race (aOR: 2.96, 95% CI: 1.70–5.12), Hispanic ethnicity (aOR: 2.11, 95% CI: 1.12–4.00), and increasing age (aOR: 1.07, 95% CI: 1.02–1.12) were significantly associated with an increased risk of GDM in the subsequent pregnancy.Conclusion An elevated 1-hour GCT in a nondiabetic index pregnancy is associated with a fourfold increased risk of GDM in a subsequent pregnancy.Key Points
Keywords: elevated glucose tolerance; screening tests; gestational diabetes; pregnancy outcomes; risk factors for gestational diabetes